Impact of X‐irradiation on microglia. Issue 1 (10th October 2017) - Menzel, Franziska; Kaiser, Nicole; Haehnel, Susann; Rapp, Felicitas; Patties, Ina; Schöneberg, Nina; Haimon, Zhana; Immig, Kerstin; Bechmann, Ingo
Abstract: Irradiation is widely used to treat brain tumors, and also to create bone marrow (BM) chimeras. BM chimeras are widely used to dissect functions and origin of microglia and blood‐derived mononuclear cells under homeostatic or pathological conditions. This is facilitated by the fact that microglia survive irradiation and are thus regarded radio‐resistant. In this study, we tested whether microglia are indeed radio‐resistant and looked for potential mechanisms that might explain this phenomenon. We analyzed the radio‐resistance of microglia independently of their physiological brain environment compared to other mononuclear cells from spleen and brain after X‐irradiation with 7 Gy or 30 Gy. Furthermore, we investigated long‐term effects of X‐irradiation on microglia using organotypic hippocampal slice cultures (OHSCs). We found a significant higher survival rate of isolated microglia 4 hr after X‐irradiation with 30 Gy accompanied by a decreased proliferation rate. Investigations of apoptosis‐related genes revealed no regulation of a specific antiapoptotic pathway but ataxia telangiectasia mutated (ATM), a DNA‐repair‐related gene, was significantly upregulated in isolated microglia 4 hr after 30 Gy. Irradiation of OHSCs with 7 and 30 Gy revealed a highly and significantly decreased cell number, morphological changes and an increase in migration velocity of microglia. Furthermore, cell loss, increased soma size and process length of microglia was also found in BM chimeras irradiated with 9.5 Gy 5 weeks after irradiation. Here, we present new evidence implying that microglia are not a homogeneous population of radio‐resistant cells and report on long‐term alterations of microglia that survived irradiation. Main Points: Microglia are regarded as "radio‐resistant" as they survive irradiation at doses used for the creation of bone marrow chimeras. We show that microglial numbers, form, and function are altered after irradiation.